Intensification of petroleum elimination in the presence of a surfactant using anodic electrochemical treatment with BDD anode - Escalona-Durán, Florymar; Villegas-Guzman, Paola; dos Santos, Elisama Vieira; da Silva, Djalma Ribeiro; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2019)
In this work, the effect of the SDS surfactant during the electrochemical treatment of water-oil effluent, using BDD anode, was studied. Different current densities and surfactant concentrations were evaluated. A satisfactory elimination of organic matter (in terms of COD) was achieved, at higher currents densities (40 and 60 mA cm−2) reaching over 94%, regardless of the supporting electrolyte used. Experiments carried out at higher current density (60 mA cm−2) in the presence of different amounts of SDS (175, 200, 500 and 1000 ppm) achieved promising results to eliminate pollutants from effluent. A favorable degradation of the organic matter was reached in the presence of 500 ppm of SDS (over 94% of COD removal). This is an excellent result considering that the initial COD increased 1.7-folds with the addition of SDS, respect to the system in the absence of surfactant. No relevant efficiencies were achieved when the SDS concentration was increased from 500 to 1000 ppm, suggesting that there is a critical concentration of SDS in which the positive effect overpass the limit associated to the addition of extra organic matter. A comparison between two supporting electrolytes (Na2SO4 and HClO4) confirmed that sulfate species are released from the SDS, producing electrochemically, persulfate. These species favored the degradation of organic matter, in which a synergic effect with the initial Na2SO4 can be identified. Results clearly indicate that the presence of SDS can be a promising approach for treating organic contaminants of low solubility, such as, in the case of water-oil effluent.
Keywords: Boron doped diamond; Electrochemical degradation; Persulfate; Synergic effect; Water-oil effluent